2015
DOI: 10.3402/edui.v6.24277
|View full text |Cite
|
Sign up to set email alerts
|

Students in higher education with reading and writing difficulties

Abstract: The aim of this study is to explore adult students' descriptions and understandings of their reading and writing difficulties, and to describe the ways they are copying with them. In higher level studies, information is typically gained by reading and giving evidence of knowledge acquisition in writing. When students have difficulties with these essential academic skills, studying and lifelong learning can be hard work as well as time-consuming. General understanding of dyslexia and reading difficulties at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…Both the discrepancy and equality of the assessments highlight the need for supporting students experiencing dyslexia-like difficulties who may have not received formal assistance and support due to the lack of documented history of learning difficulties. It further indicates that reading problems constitute a real issue that should be taken into account when we think about appropriate student services (Pirttimaa et al, 2015 ; Quick, 2013 ; Reis et al, 2020 ). Individuals without a formal diagnosis of dyslexia may have not obtained it at the elementary-school level because of a mild severity of their problems and the failure to meet all diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Both the discrepancy and equality of the assessments highlight the need for supporting students experiencing dyslexia-like difficulties who may have not received formal assistance and support due to the lack of documented history of learning difficulties. It further indicates that reading problems constitute a real issue that should be taken into account when we think about appropriate student services (Pirttimaa et al, 2015 ; Quick, 2013 ; Reis et al, 2020 ). Individuals without a formal diagnosis of dyslexia may have not obtained it at the elementary-school level because of a mild severity of their problems and the failure to meet all diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence to indicate that children with social, emotional and behavioural difficulties do not receive sufficient support at school (Botha & Kourkoutas, 2016;Giota & Lundborg, 2007;Lane, 2007;Persson, 2004). Other studies have reported that children who experience difficulties with regards to reading and writing also move through their school careers without receiving adequate support (e.g., Pirttimaa, Takala, & Ladonlahti, 2015). In terms of students who experience difficulties with mathematics, there is currently a lack of evidence concerning the effectiveness of teachers' efforts (Engström, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The IDA ( 2017 ) reiterate that the symptoms of dyslexia include confusion with words that start with the letters b, p, d or g, memorising numbers and words, slow and laboured comprehension, and problems with arithmetical calculations and remembering days of the week in sequence or letters of the alphabet. Pirttimaa et al ( 2015 ) reiterate that dyslexia is mainly caused by problems in phonological coding and the persistence of poor phonological skills. This idea is supported by Elbro and Scarborough ( 2004 ), who state that problems with phonological decoding and other challenges in phonological ability seem to be the core deficit in dyslexia.…”
Section: Introductionmentioning
confidence: 99%